Antioxidant Effect of Lycopersicum esculentum on Plasma Superoxide Dismutase, Catalase and Malondialdehyde in Rat Espoused with Lead Acetate - A Khaki (Institue of Medicinal Plants, ACECR, 2011)
Background: Lead, an example of heavy metals, has, for decades, being known for its adverse effects on various body organs and systems such that their functions are compromised. Objective: In the present study, the ability of Lycopersicum esculentum on decrease toxic effects of lead acetate on plasma superoxide dismutase, catalase and malondialdehyde in Rat. Lead to adversely affect the Liver tissue apoptosis was investigated and Lycopersicum esculentum: Source of antioxidants was administered orally to prevent the adverse effects of Pb. Methods: Eighteen wistar rats, randomized into three groups (n = 6), were used for this study. Animals in Group A served as the control and was drinking distilled water. Animals in Groups B and C were drinking 1% Lead acetate (LA). Group C animals were, in addition to drinking LA, treated with 1.5 ml of Lycopersicum esculentum /day. All treatments were for 10 weeks. Results: The obtained results showed that Pb caused a significant reduction in the liver weight, plasma and tissue superoxide dismutase and catalase activity, but a significant increase in plasma malondialdehyde concentration. Conclusion: These findings lead to the conclusion that Lycopersicum esculentum significantly lowered the adverse effects of Pb oxidative stress.